2014
DOI: 10.1007/430_2013_139
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Structures and Bonding in Metal-Coated Gold Nanorods

Abstract: We present a topical review of research in the field of metal-coated gold nanorods. By combining synthetic design strategies with state-of-the art characterisation techniques (particularly aberration-corrected scanning transmission electron microscopy) and molecular dynamic simulations, we demonstrate the potential to gain a fundamental understanding of, and control over, the atomic detail of metalmetal bonding at the interfaces of core-shell nanorods and nanoparticles. This analysis is facilitated by making c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 89 publications
(103 reference statements)
0
8
0
1
Order By: Relevance
“…Although several groups have succeeded in synthesizing solid-solution nanoalloys of bulk-immiscible elements using colloidal methods 11 13 14 , these structures are generally metastable and cannot resist the thermal treatment needed for removing the stabilizing agents. As the thermodynamic properties of bulk alloys can influence the structure of their nanosized counterparts, some of us have recently compared the well-known bulk-miscible Au-Pd system 7 12 16 to the rarely studied bulk-immiscible Au-Rh system 11 13 17 in terms of mixing behaviour and reactivity at the nanoscale 9 15 18 . As seen for 3 nm-sized nanoparticles (NPs) anchored on well-defined rutile titania nanorods, Au and Pd atoms form a solid-solution alloy, whilst Au and Rh atoms segregate into single-phase domains within the NPs 15 .…”
mentioning
confidence: 99%
“…Although several groups have succeeded in synthesizing solid-solution nanoalloys of bulk-immiscible elements using colloidal methods 11 13 14 , these structures are generally metastable and cannot resist the thermal treatment needed for removing the stabilizing agents. As the thermodynamic properties of bulk alloys can influence the structure of their nanosized counterparts, some of us have recently compared the well-known bulk-miscible Au-Pd system 7 12 16 to the rarely studied bulk-immiscible Au-Rh system 11 13 17 in terms of mixing behaviour and reactivity at the nanoscale 9 15 18 . As seen for 3 nm-sized nanoparticles (NPs) anchored on well-defined rutile titania nanorods, Au and Pd atoms form a solid-solution alloy, whilst Au and Rh atoms segregate into single-phase domains within the NPs 15 .…”
mentioning
confidence: 99%
“…The complex behavior observed for Au–Rh clusters could be better understood by characterizing the alloying/segregation phenomena on well-defined surfaces. While computational analysis of the interaction of Au with Rh(111) is the subject of the present paper as a continuation of our recent experimental studies, , other relevant surfaces were addressed in previous works. ,, Scanning tunneling microscopy (STM) and Auger electron spectroscopy (AES) investigations showed that Rh forms three-dimensional (3D) islands on Au(111) at room temperature according to Volmer–Weber growth. Annealing to 673 K induced the immersion or encapsulation of Rh islands in the topmost atomic layer of the substrate, and the removed Au atoms covered the Rh islands .…”
Section: Introductionmentioning
confidence: 89%
“…When Au adatoms were also added to the simulation at 500 K, their stabilization at the perimeter/on top of Rh clusters were shown. 24,34 DFT calculations and molecular dynamics simulations indicated no significant distortion of the Rh(100) substrate atoms, when a small Au platelet consisting of 13 atoms was placed on top forming an ordered adlayer. 28 Christensen et al calculated the first and second derivatives of the surface energy as a function of impurity (added metal) surface molar fraction in the zero-concentration limit, i.e.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Pure gold clusters have been intensively studied in recent years due to their novel properties at the nanoscale. [1,2,3,4,5,6,7] It is known that relativistic effects on the electrons in gold lead to the hybridization of the 6s and 5d orbitals which generates several interesting properties such as the well documented 2dimensionality of cluster structures up to 13 atoms. [8,9,10,11,12,13,14] Gold clusters have been proposed for catalysis because of their high reactivity, partly due to the high surface to volume ratio.…”
Section: Introductionmentioning
confidence: 99%